Mechanism of Hindu Datura in the Treatment of Rheumatoid Arthritis from the Perspective of Network Pharmacology - Changlong FU; Yangyang MEI; Xihai LI; Zhiwei QIU; Changxing CHEN; Chunsong ZHENG (康复学报)
Objective:To construct the active component target of Hindu datura and the disease target of rheumatoid arthritis by using network pharmacology, to predict the specific molecular signal and pathway of hindu datura in the treatment of rheumatoid arthritis, and to analyze its potential therapeutic target and molecular mechanism.Methods:All the chemical components of hindu datura were summarized and screened through Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform(TCMSP)database, retrieval was performed with the preset oral bioavailability(OB)≥30%and drug like(DL)≥0.18.Uniprot database was used to screen the entire correlation basis of the effective chemical compound.After screening the disease target with"rheumatoid arthritis"as the retrieval word using GeneCards and OMIM database, the superimposed target area between the drug target of hindu datura and the disease target of rheumatoid arthritis was summarized and analyzed, and it could be used as the prediction target gene of hindu datura for treating rheumatoid arthritis.Network targets were constructed and analyzed for the exported data based on Cytoscape 3.7.1 software and STRING 7.8 database.Finally, GO functional enrichment analysis and KEGG signal pathway analysis were performed to further screen the main targets and signal pathways.Results:①Through screening and analysis, 27 effective compounds, 318 corresponding target genes and 125 predicted target genes were obtained for the treatment of rheumatoid arthritis.②The core genes in PPI network mainly included JUN, AKT1, RELA, MAPK1, etc.③GO functional enrichment analysis showed that the biological process(BP)for the treatment of rheumatoid arthritis by hindu datura mainly involves response to lipopolysaccharide, response to lipopolysaccharide, response to molecule of bacterial origin, response to metalion, response to oxidative stress, response to steroid hormone, cellular response to oxidative stress, reactive oxygen species metabolic process, response to oxygen levels, etc..The cell component(CC)consisted of membrane raft, membrane region, plasma membrane raft and presynaptic membrane; molecular functions(MF)mainly involved the nuclear receptor activity, transcription factor activity(direct ligand regulated sequence-specific DNA binding), steroid hormone receptor activity, cytokine receptors, cytokine activity, DNA-binding transcription activator activity, RNA polymeraseⅡtranscription factor binding, kinase regulator activity, receptor ligand activity, etc.The analysis of KEGG signaling pathway showed that the obvious pathway of hindu datura in the treatment of rheumatoid arthritis may involve IL-17 signaling pathway, TNF signal pathway, HIF-1signalpathway, Toll-like receptor signal pathway, etc.Conclusion:The potential mechanism of hindu datura for the treatment of rheumatoid arthritis is to exert anti-inflammatory, analgesic and antioxidant effects, which involve a number of interactive signal pathways.